The Changing Face of Rural Kediri: A Study on Rural Transformation Processes - Dixzi Anindita Sandy (The Indonesian Journal of Planning and Development, 2023)
Urbanization, along with the flow of various elements, has triggered changes in the economic, social, and spatial structures of many regions, driving processes of rural transformation. This transformation presents challenges for both rural and urban development due to its broad impact on physical, socio-economic, and cultural aspects. Kediri Regency, located on Java Island, has experienced such changes, with 29 villages reclassified as urban between 2000 and 2010, based on BPS Regulation No. 37 of 2010—indicating a clear sign of rural transformation. This study aims to assess the degree of rural transformation in Kediri Regency by analyzing physical, economic, and socio-demographic aspects. The research uses spatial and socio-economic data from 2013 and 2023, analyzed through descriptive quantitative methods, GIS, and a weighted scoring analysis. Findings show that all three studied villages—Bringin, Gempolan, and Petok—have undergone varying levels of transformation. Bringin displays the most significant economic and socio-demographic transformation, driven by growth in non-agricultural employment, household income, and access to education and health services. Gempolan ranks highest in overall transformation due to industrial growth, land-use changes, and expanded infrastructure and services. In contrast, Petok shows minimal transformation, particularly in economic and physical aspects, with stagnant development indicators. Overall, rural transformation is most advanced in Bringin, likely due to its proximity to Pare, a secondary city, which stimulates rural change through increased urban economic interaction.